PENGARUH QUALITY OF WORK LIFE, DISIPLIN KERJA, DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA GURU: STUDI KASUS DI SD KECAMATAN PAMULANG GUGUS 12 TANGERANG SELATAN - Luthfie, Ocha Mardhina; Anwar, Saiful; Zubaidah, Siti (Jurnal Manajemen Pendidikan, 2025)
Objective: This study aims to analyze the direct and indirect effects of Quality of Work Life (QWL) and Transformational Leadership on Teacher Performance, with Work Discipline as a mediating variable, in Public Elementary Schools in Pamulang District. Methods: The research employs an explanatory quantitative approach with a survey method. A sample of 144 teachers from 12 accredited A elementary schools was selected through proportional random sampling. Data were collected using validated questionnaires and analyzed using Path Analysis to test the causal relationships between variables. Results: (1) QWL, Work Discipline, and Transformational Leadership have a positive and significant direct effect on Teacher Performance; (2) Work Discipline has the dominant direct influence (0.766); (3) QWL and Transformational Leadership significantly strengthen Work Discipline; (4) Work Discipline acts as an effective partial mediator, where the indirect effects of QWL (0.280) and Transformational Leadership (0.503) on performance through this mediator are greater than their direct effects. Novelty: The biggest impact of Transformational Leadership and QWL on Teacher Performance is transmitted through Work Discipline.